2008
DOI: 10.2137/1239099042643107
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between climate and winter cereal grain quality in Finland and their potential for forecasting

Abstract: Many studies have demonstrated the effects of climate on cereal yield, but there has been little work carried out examining the relationships between climate and cereal grain quality on a national scale. In this study national mean hectolitre weight for both rye and winter wheat in Finland was modelled using monthly gridded accumulated snow depth, precipitation rate, solar radiation and temperature over the period 1971 to 2001. Variables with significant relationships in correlation analysis both before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…A previous study [57] has found, for basically the same data set, that high yields were related to high February temperatures and were less significantly related to January temperatures, indicating that the relationship of temperature to yield depends on the way in which the effects of temperature on the crop are expressed. The apparent absence of a correlation between yield and number of days with drought in Sweden is in agreement with other studies, which have seldom found clear relationships between the precipitation in specific months from March through June and winter wheat yield in Sweden [58], Denmark [59], and Finland [60]. This lack of clear relationships may be due to prevailing frequent irregular precipitation and the ability of the soils to buffer short-term water shortage.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study [57] has found, for basically the same data set, that high yields were related to high February temperatures and were less significantly related to January temperatures, indicating that the relationship of temperature to yield depends on the way in which the effects of temperature on the crop are expressed. The apparent absence of a correlation between yield and number of days with drought in Sweden is in agreement with other studies, which have seldom found clear relationships between the precipitation in specific months from March through June and winter wheat yield in Sweden [58], Denmark [59], and Finland [60]. This lack of clear relationships may be due to prevailing frequent irregular precipitation and the ability of the soils to buffer short-term water shortage.…”
Section: Discussionsupporting
confidence: 90%
“…Hectolitre weight is a grain quality indicator and is the weight of a fixed volume of grain (kg hL )1 ). It is used as an approximate measure of the expected flour yield (Hollins et al, 2004). Generally greater the hectolitre weight, better the quality and yield of flour (Kunert et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Hectolitre weight is a grain quality indicator and is the weight of a fixed volume of grain (kg hL −1 ). It is used as an approximate measure of the expected flour yield (Hollins et al. , 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Finland is often considered to be the most northern agricultural country in the world (e.g. Mukula and Rantanen 1987;Häkkilä 2002;Hollins et al 2004), where hunger, frost and crop failures constitute recurring themes in the narratives of its agricultural history (e.g. Jutikkala 2003;Solantie 2006;Lappalainen 2012).…”
Section: Introductionmentioning
confidence: 99%